Avaliação do impacto do programa de apoio a planos de reestruturação e expansão das Universidades Federais (REUNI) no sistema de Bibliotecas Universitárias da Universidade Federal do Ceará - Mesquita, Margareth de Figueiredo Nogueira (2016)
This study carried out an impact evaluation of the Support Program to the Plans of Restructuring and Expanding the Federal Universities – REUNI directed to the University Library System – SBU at Federal University of Ceará – UFC. It has as goal to identify the enhancements occurred in the UFC’s Library System during the last seven years, especially those resulting from the implementation of the REUNI Program. This research is exploratory of the documental kind and its relevance is due to the identification of the improvements occurring in the Library System of the UFC as result of the REUNI, to the extent of being able to reveal whether the strength of the Law of the Evaluation System of Higher Education (SINAES), no. 10.861 from April 14th of 2004, as a tool to improve the SBU. Thus, we analyzed the UFC’s investments applied to that system, comparing them with those made from the installation onward. The data were about the actions and inversions in the period from 2001 to 2006, before the REUNI, when the evaluation system, SINAES, still was taking the first steps at the federal institution of higher education. The data were compared to the inversions from 2007 to 2014, which was born from the REUNI and analyzed by this study. The results showed that the REUNI was a relevant factor and an effective tool to both, the modernization of the library systems and its management in the UFC, and that somehow SINAES has contributed to the improvement and the increase in the collection of the University Libraries System.